A1.44 Fibroblasts lose their immunosuppressive ability early in the development of rheumatoid arthritis: effects on lymphocyte recruitment. (31st January 2014) - McGettrick, Helen M; Filer, Andrew; Raza, Karim; Nash, Gerard B; Buckley, Christopher D
Abstract : Objectives: Fibroblasts actively regulate the recruitment of leukocytes by endothelial cells (EC), acting in a pro- or anti-inflammatory manner depending on their site of origin. The phenotype of the fibroblast may be a critical determinant of whether leukocyte recruitment, and therefore inflammation, resolves or persists. Here we examined how synovial fibroblasts from different stages of arthritis influenced the recruitment of peripheral blood lymphocytes (PBL) and their onward migration. Methods: Fibroblasts were isolated from patients with resolving or persistent arthritis. Rheumatoid arthritis (RA) cohorts were categorised based on the stage of disease at the time of sample collection: very early (≤ 12wk duration); newly presented established (>12 wk duration) or long established undergoing replacement surgery. Endothelial-fibroblast co-cultures were formed on either side of porous filters, and PBL adhesion was assessed using phase-contrast microscopy. Results: Rheumatoid fibroblasts increased PBL recruitment in a disease duration-dependent manner (early RA <newly established <established, replacement). However, similar levels of binding were observed when fibroblasts from resolving or early RA tissue were incorporated. These data indicate that early RA and established, replacement fibroblasts have distinct phenotypes, where fibroblast in early RA have yet to acquire the ability to stimulate recruitment. When exogenous cytokines were added, co-cultures incorporating fibroblasts from resolving tissues suppressed PBL recruitment in an IL-6 and TGF-b dependent manner. Interestingly this immunosuppressive effect was lost in early RA, indicating that these fibroblasts lose their immunosuppressive phenotype early in disease development. Moreover, the mode of action of IL-6 and TGFb are hijacked in early RA, such that they no long suppress recruitment supporting aberrant lymphocyte infiltration. Conclusions: Fibroblasts from acutely resolving and early persistent arthritis are distinct. The latter lose immunosuppressive capability and acquire modifications towards a pro-inflammatory phenotype early in the disease process, even before clinical criteria are fulfilled. They may thus induce recruitment or inappropriately support cytokine-driven recruitment, leading to an accumulation of PBL in the rheumatoid joint.